Effects of Iron Supplementation and Nutrition Education on Adolescent Girls' Knowledge, Adherence, and Hemoglobin Levels - Fatmawati; St. Masithah; Siti Uswatun Hasanah; Andi Rahmaniar MB (Politeknik Kesehatan Kemenkes Surabaya, 2026)
Anemia remains a major public health problem among adolescent girls in Indonesia. The effectiveness of iron supplementation programs is often constrained by inadequate knowledge and poor adherence to iron tablet consumption. This study analyzed the effects of iron supplementation integrated with nutrition education on knowledge, adherence, and hemoglobin (Hb) levels among adolescent girls. A quasi-experimental pretest-posttest control group design was conducted among 56 adolescent girls from four senior high schools in Maros Regency, Indonesia, using multistage cluster random sampling, with two schools allocated to an intervention group (n = 27, iron supplementation plus nutrition education) and two schools to a control group (n = 29, iron supplementation only). Baseline knowledge scores did not differ significantly between groups (p = 0.115); adherence was not assessed at baseline, as it was a prospective outcome measured throughout the intervention using the DOS method. Data were analyzed using the Wilcoxon, Mann-Whitney, paired t-test, and ANCOVA, with baseline hemoglobin, dietary intake, nutritional status, and menstrual cycle as covariates. Knowledge increased significantly in the intervention group (p < 0.001), with significant between-group differences in knowledge (p < 0.001) and adherence (92.6% vs. 44.8%; p = 0.002). Mean Hb rose significantly in the intervention group, from 13.12 ± 1.78 to 14.15 ± 1.35 g/dL (p = 0.011). Adjusted Hb remained significantly higher in the intervention than control (13.86 vs. 12.90 g/dL; F = 6.065; p = 0.017). Integrating nutrition education into iron supplementation programs improved knowledge, adherence, and Hb levels, supporting incorporation into school-based anemia prevention efforts.